The role of company’s website characteristics in enhancing the B2B customer experience - Ribeiro, Liliana Sofia Castro (2022)
Enhancing the business-to-business (B2B) customer experience is a priority for B2B companies. Improving communications and marketing tools such as the company website is one important way to enhance this experience and attract and persuade customers to engage with B2B companies. Relying on the case of Amorim Top Series company, this study aimed to understand the impact of B2B website characteristics on brand credibility and customer loyalty, considering the mediating role of customer satisfaction and engagement. The research model was built by reviewing the literature and acknowledging seven factors that are expected to influence customer satisfaction and engagement, brand credibility, and customer loyalty. To test the proposed model, an online survey-based study comprising a final sample size of 107 Amorim Top Series customers has been conducted. Data were analyzed using SPSS. To test the direct hypotheses, regression analysis was performed while the Sobel test was used to examine the mediating hypotheses. The results indicated that B2B website characteristics have a direct effect on customer satisfaction and engagement with the brand, and these two factors mediate the relationship between B2B website characteristics, on the one hand, and credibility and loyalty, on the other. Based on these findings, theoretical contributions were discussed and managerial implications on how to effectively improve B2B websites were provided.